Penerapan Contextual Teaching and Learning untuk Meningkatkan Penguasaan Konsep Siswa Materi Sila-Sila Pancasila - Mirda Widya Astutik; Arya Setya Nugroho; Nataria Wahyuning Subayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The aim of the research is to determine the increase in students' mastery of concepts through the application of CTL to the Pancasila precepts material, to find out the activities of teachers and students in the learning process using CTL to increase concept mastery in the Pancasila precepts material. The research was carried out in second grade at UPT SDN 98 Gresik. Classroom action research is designed in one cycle through four stages, namely: planning, action, observation, and reflection. The data analysis technique uses initial data on students' concept mastery before applying CTL and the results of students' concept mastery after applying CTL. Data collection techniques used observation, tests and assessment grids of mastery of the concept indicators. The results of the study after applying CTL one cycle showed an increase in students' mastery of concepts. Student activity during the learning process obtained a score of 83.3% as many as 25 students who completed, while 5 students had not completed or 16.7%, the results were categorized as complete because more than 75%. The teacher's activity in the learning process was achieved with a result of 85.7% with a good score.